48th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2012
DOI: 10.2514/6.2012-4029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Cavitation Induced Feedline Instability from an Orifice

Abstract: T his paper details the results of an experimental investigation into the cavitation instabilities created by a circular orifice conducted at the University of A labama in H untsville Propulsion Resea rch C enter. T his experiment was conducted in concert with a computational simulation to serve as a reference point for the simulation. T esting was conducted using liquid nitrogen as a cryogenic propellant simulant. A 1.06 cm diameter thin orifice with a rounded inlet was tested in an approximately 1.25 kg/s fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…Statistical analysis based on Fast Fourier transform (FFT) and on wavelet transform was widely used in signal processing showing good performances for analysis of these signals. Fast Fourier Transforms were performed on the high frequency data acquired by pressure sensors to determine the instability frequency related to the development of cryogenic cavitation in an orifice [9]. In [10] the power spectral density (PSD), and the probability density function (PDF) of the void-fraction signal from a capacitance sensors were used to objectively identify the flow pattern in two phase flows.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis based on Fast Fourier transform (FFT) and on wavelet transform was widely used in signal processing showing good performances for analysis of these signals. Fast Fourier Transforms were performed on the high frequency data acquired by pressure sensors to determine the instability frequency related to the development of cryogenic cavitation in an orifice [9]. In [10] the power spectral density (PSD), and the probability density function (PDF) of the void-fraction signal from a capacitance sensors were used to objectively identify the flow pattern in two phase flows.…”
Section: Introductionmentioning
confidence: 99%
“…12. For this load point dominant peaks are present which match to the 1L mode frequency range, but most importantly the frequency of the 1L mode of the post yields in this case Strouhal numbers around 0.35, which is in the range where acoustic excitation due to orifice whistling phenomena have been described in literature [30][31][32]. Therefore it is possible that hydrodynamic effects as periodic vortex shedding at the LOX post throttle orifice excites the LOX posts or at least may amplify the acoustic oscillations in the LOX post.…”
Section: Preliminary Analysis Of Lox Post Acoustics Sourcementioning
confidence: 73%
“…Typical Strouhal number values for orifice flow hydrodynamics exciting the tube acoustic eigenmodes are in the range 0.2-0.35 [30]. Hitt et al found a maximum response for the flow of cryogenic nitrogen through a thin orifice at a Strouhal number of 0.28 ± 10 % [31]. The investigation of Lacombe et al [32] came to the result that acoustic amplification due to orifice whistling can be observed in the range 0.2 to 0.4.…”
Section: Preliminary Analysis Of Lox Post Acoustics Sourcementioning
confidence: 99%
“…Statistical analysis based on Fast Fourier transform (FFT) and on wavelet transform was widely used in signal processing showing good performances for analysis of these signals. In [10] Fast Fourier Transforms was applied to the pressure fluctuations generated in the orifice in presence of cryogenic cavitation to investigate the related instability frequency.…”
Section: Introductionmentioning
confidence: 99%